“You First Have to Check Out the Doctors”: Transition Expectations and Experiences of Survivors After Pediatric Cancer - Aleshchenko, Ekaterina; Langer, Thorsten; Calaminus, Gabriele; Glogner, Juliane; Haugke, Henrike; Trocchi, Pietro; Swart, Enno; Baust, Katja (Cancer medicine (Malden, MA), 2024)
ABSTRACT Purpose The shift from child‐centered to adult‐focused healthcare presents social and psychological challenges for adolescents and young adults with chronic conditions, which can affect their participation in follow‐up care. This study aims to investigate the factors that influence patient‐driven motivations for adhering to follow‐up recommendations, while also exploring the barriers and supports that impact the transition process for pediatric cancer survivors. Methods We developed interview guidelines grounded in the Theory of Planned Behavior (TPB) and the stereotype priming model (SPM). We conducted 10 episodic narrative interviews with pediatric cancer survivors during their transition phase. The interview transcripts were analyzed through qualitative thematic content analysis, followed by quantitative analysis using multiple regression models. This research is a part of the broader VersKiK study, which aims to propose enhancements to the organization of (long‐term) follow‐up care after cancer in childhood and adolescence in Germany. Results In this study, pediatric cancer survivors transitioning to adult healthcare showed varied motivations for follow‐up care. Positive attitudes, driven by understanding the benefits, improved engagement, while anxiety and fear of losing familiar care created barriers. Family and peer support played a key role in encouraging adherence. Perceived control over healthcare management, supported by organizational help, was crucial, but logistical and financial challenges often undermined this control. Conclusions Several motives underlying pediatric cancer survivors' behavior significantly influence their transition experiences. Enhancing positive attitudes, strengthening social support, and improving perceived control through targeted interventions may support smoother transitions to adult healthcare facilities. Trial Registration: Registered at German Clinical Trial Register (IDs: DRKS00025960 and DRKS00026092)